Decision Support System for Determining Smart Fishery Village Tourism Development Priorities Using AHP and TOPSIS Methods - Jefri Putri Nugraha; Djoko Surahmat; Wahyu Puji Astiyani; Nasrun Nasrun; Mula Tumpu; Nova Magdalena Tumanduk; Rakhma Fitria Larasati (Dinasti Publisher, 2025)
The objective of this research is to obtain accurate results in determining the development of the Smart Fisheries Village as a superior tourist destination, through the implementation of a decision support system using AHP (Analytic Hierarchy Process) and the Order Preference by Similarity to Ideal Solution Method (TOPSIS) technique. This research was carried out in 5 village-based Smart Fisheries Village locations spread across several areas of East Java using descriptive qualitative research methods. Based on the results of the analysis that has been carried out, the village SFV results are obtained is at the pilot tourism village level, namely SFV Kendalbulur Village; at the developing tourist village level are SFV Sumberdodol Village and SFV Mangunegara Village; and at the advanced tourism village level are SFV Panembangan Village and SFV Kawali Village